2018
DOI: 10.1101/342634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbial Dysbiosis and polyamine metabolism as predictive markers for early detection of pancreatic cancer

Abstract: Synopsis:Gut microbiota changes during early stages of pancreatic ductal adenocarcinoma (PDAC) progression and contributes towards host polyamine pool. Both changes can be used as an early predictive marker for PDAC. Short title: Whole genome sequencing of PDAC microbiomeWord count: 4,735 Translational RelevancePancreatic carcinogenesis progresses through pre-cancerous PanIN lesions to invasive cancer. Even though these morphological changes are histologically distinct, imaging techniques are not able to di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 65 publications
0
8
0
1
Order By: Relevance
“…Moreover, polyamines such as cadaverine and putrescine showed a higher abundance in the CRC group with respect to the healthy cohort, suggesting a role as potential biomarkers [ 50 ]. Along with these aspects, studies on pancreatic ductal adenocarcinoma (PDAC) in mouse models have showed that the early dysbiosis occurrence is responsible for the high concentration of polyamines in PDAC mice and patients, suggesting the possibility to measure these metabolites for early detection purposes [ 51 ].…”
Section: Proteins: Polyamines (Pas)mentioning
confidence: 99%
“…Moreover, polyamines such as cadaverine and putrescine showed a higher abundance in the CRC group with respect to the healthy cohort, suggesting a role as potential biomarkers [ 50 ]. Along with these aspects, studies on pancreatic ductal adenocarcinoma (PDAC) in mouse models have showed that the early dysbiosis occurrence is responsible for the high concentration of polyamines in PDAC mice and patients, suggesting the possibility to measure these metabolites for early detection purposes [ 51 ].…”
Section: Proteins: Polyamines (Pas)mentioning
confidence: 99%
“…In an animal study, Mendez et al [151] demonstrated a substantial correlation between microbial dysbiosis and the release of tumor-inducing metabolites in the earlystage, while showing significantly elevated serum polyamine concentrations in PDAC patients; this may be postulated as a predictive biomarker for early detection of pancreatic cancer. It is among the current assumptions that bacteria in the pancreatic microbiome may contribute to the resistance of gemcitabine, which is widely used in the treatment of PDAC.…”
Section: Metagenomic Biomarkers Of Pancreatic Cancermentioning
confidence: 99%
“…A mikrobiom és a PA közötti kapcsolat ötlete először akkor merült fel, amikor felfedezték, hogy a Helicobacter pylorikolonizáció pancreatitishez társul (27). Azóta több hasonló összefüggést mutattak ki a szájüreg (28), a bélrendszer (29), a pancreas (18,30,31) és a széklet (20,32) mikrobiomja, a mycobiom (33) és a PA között. Jelenlegi ismereteink szerint a szájüregi-, gyomor-és bélmikrobiom alkotórészei gyulladást kelthetnek.…”
Section: Onkobiom Pancreas-adenocarcinomábanunclassified